TANGGUNG JAWAB PIDANA BAGI PELAKU YANG MENGGUNAKAN BAHAN BAKU KEDALUWARSA - Erlina Dwi Susanti; Ahmad Mahyani (Gapenas Publisher, 2023)
This article or article aims to discuss criminal responsibility for the perpetrators of using expired raw materials using the Study of Decision Number 284/Pid.Sus/2019/PN.Mjk. The defendant is an owner of UD. BAROKAH which is engaged in the production of super instant noodles stamped BUNGA TROMPET. Implementation of activities or processes of production, storage, transportation, and distribution of super instant noodle food, the Defendant used raw materials by purchasing expired instant noodle raw materials, then reprocessing them like instant noodle processing in general, but the raw materials used where default has expired. Then the instant noodles are repackaged using plastic packaging and labeled super instant noodles stamp BUNGA TROMPET. The method used in this research is normative juridical or legal research, namely research that is focused on examining the application of rules or norms in positive law. This research was conducted by examining various formal legal regulations such as laws, as well as literature containing theoretical concepts related to the problems discussed in writing. This study concludes that corporate criminal liability is still a problem that needs to be resolved. Likewise, the issue of criminal liability to corporations in criminal acts in the field of consumer protection still contains many weaknesses. As well as the Decision Number 284/Pid.Sus/2019/PN.Mjk has a deterrent effect on the Defendant. However, the actions of Defendant can still fulfill the elements of Article 11 letters a and b of the UUPK. As well as labeling the noodles as if they were edible and safe for health